Evaluation of the Immune Response of a Candidate Phage-Based Vaccine against Rhipicephalus microplus (Cattle Tick) - Alejandro González-Mora; Kenny Misael Calvillo-Rodríguez; Jesús Hernández-Pérez; Marco Rito-Palomares; Ana Carolina Martínez-Torres; Jorge Benavides (MDPI AG, 2021)
Cattle tick (Rhipicephalus microplus) represents a severe problem causing substantial economic losses, estimated in billions of dollars annually. Currently, chemical acaricides represent the most widely used control method. However, several problems such as resistance have been described. Phage-based vaccines represent a fast and low-cost tool for antigen delivery. In this regard, the objective of the present work was to develop a candidate phage-based vaccine displaying a cattle tick antigen (Bm86-derived Sbm7462 antigen) on the surface of bacteriophage M13. Phage ELISA and dot blotting analysis confirmed the display of the antigen. Vaccine immunogenicity was evaluated using a bovine monocyte-derived dendritic cell-based ex vivo assay and a murine in vivo assay. The ex vivo model showed the maturation of dendritic cells after being pulsed with the phage-based vaccine. The humoral response was confirmed in the in vivo assay. These results demonstrated the capacity of the phage-based vaccine to induce both humoral and cellular immune-specific responses. Importantly, this is the first report describing a control method for cattle ticks using a candidate phage-based vaccine. Further studies to evaluate the immunogenicity in a bovine model are needed. The current approach represents a promising alternative to control cattle tick infestations.